UNLOCKING THE POTENTIALS OF WORK-LIFE BALANCE IN GOVERNMENT PARASTATALS IN NIGERIA - Maxwell Nwinye (American Journals Publishing, 2025)
One of the greatest benefits of a work-life balance is to make employees happy and remain with the organization. Robust work-life balance helps workers to have enjoyable life both inside and outside of work. Availability of wore-life balance boost job satisfaction, employee performance, and minimizes turnover intention among employees. When government parastatals have a good work-life balance policy, retention and productivity may certainly rise. This study concentrated on the potentials of work-life balance affecting employees in government parastatals in Nigeria. However, the neglect of organization’s work-life balance among the employees may create negative consequences towards the employees which directly hinders organizational performance. Furthermore, government parastatals should encourage a robust supervisor support behaviour and work-life balance that may increase job satisfaction, productivity, and reduce burnout among employees.
Keywords: Work-life balance, supervisor support, autonomy, job satisfaction